2016
DOI: 10.1111/fare.12189
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Parents' Dyadic Coping for Children

Abstract: Stress and coping in couples have received increased research attention during the past two decades, particularly with regard to how couples cope with stress. Dyadic coping has emerged as a strong predictor of relationship satisfaction. Less research has focused on the effects of dyadic coping on other outcomes or family members. In the present study, the authors addressed this gap by examining parents' dyadic coping as a predictor of children's internalizing symptoms, externalizing symptoms, and prosocial beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 38 publications
0
38
1
1
Order By: Relevance
“…This study was approved by the local ethics committee. The current data set has already been used in other publications (e.g., Zemp, Bodenmann, Backes, Sutter‐Stickel, & Revenson, ), but the current results do not overlap with these published results.…”
Section: Methodsmentioning
confidence: 57%
“…This study was approved by the local ethics committee. The current data set has already been used in other publications (e.g., Zemp, Bodenmann, Backes, Sutter‐Stickel, & Revenson, ), but the current results do not overlap with these published results.…”
Section: Methodsmentioning
confidence: 57%
“…DC has also been shown to be beneficial for other family members. Zemp et al (2016) found that DC predicted lower internalizing and externalizing symptoms and higher prosocial behavior in children, with particularly stable effects for externalizing behavior.…”
Section: Overall DC (Stm)mentioning
confidence: 99%
“…They found that destructive couple conflict at baseline significantly predicted child behavior problems 1 year later (t2), but also that child behavior problems at t2 significantly predicted the extent of couple conflict another year later. While the earlier research, for example, by Schermerhorn et al (2007) and Zemp, Bodenmann, Backes, et al (2016), was conducted with families with mainly school aged children and adolescents, the foster and biological children of the present investigation were mainly of preschool age. At this point, again, longer follow-ups are needed to track the development of the DC of (foster) parents and its association with child mental health problems over a longer period of time.…”
Section: Prediction Of Children's Mental Health Scores By Maternal Anmentioning
confidence: 93%
“…If the parents lack adequate coping competencies, child-related stress may spill over to the parental relationship, impair the parental communication, and lead to a reduced relationship satisfaction in couples (Mitnick, Heyman, & Smith Slep, 2009;Zemp, Nussbeck, Cummings, & Bodenmann, 2017). Low DC competencies may also be a risk factor for child maladjustment (e.g., Zemp, Bodenmann, Backes, et al, 2016), while high DC competencies are an important protective factor for child mental health (e.g., Cina & Bodenmann, 2009;Zemp, Milek, et al, 2016).…”
Section: Dyadic Coping and Its Relation To Children's Well-beingmentioning
confidence: 99%
See 1 more Smart Citation